Biorefinery for the co-production of protein, hydrochar and additional co-products from a green seaweed Ulva sp. with subcritical water hydrolysis. (1st December 2020) - Polikovsky, Mark; Gillis, Amichai; Steinbruch, Efraim; Robin, Arthur; Epstein, Michael; Kribus, Abraham; Golberg, Alexander
Graphical abstract: Highlights: SW treatment of Ulva biomass led to the production of hydrochar and phytochemicals. SW treatment led to the extraction of 84.9% protein from the total Ulva protein. Ethanol production was optimized with S. cerevisiae and E. coli, in a two-step. 0.84% of Israel's EEZ can cover all national demand for protein by using Ulva . Abstract: Marine seaweeds are promising biomass feedstock for the co-production of food, energy and chemicals in a biorefinery. In this study, subcritical water hydrolysis (SWH) was applied to the biomass of green seaweed Ulva sp., fast-growing cosmopolitan seaweed. The SWH was done with seawater at 180 °C and 10.5 bar during 40 min with 8% w/w solid load. This treatment resulted in 211 ± 7 mg of hydrochar g −1 dry weight (DW) of Ulva sp. with higher heating value (HHV) double that of the initial biomass. The liquid fraction content per gram of Ulva DW included 5.2 ± 1.15 mg of 5-HMF; 24.1 ± 2.84 mg total monosaccharides (composed of 14.3 ± 1.78 mg glucose, 5.1 ± 0.41 mg rhamnose, 2.3 ± 0.41 mg fructose, 1 ± 0.06 mg xylose, 0.9 ± 0.08 mg galactose and 0.6 ± 0.11 mg glucuronic acid); 58 ± 11.78 mg protein (corresponding to 84.9 ± 13.2% of the total protein); and free amino acids (3.64 ± 0.07 mg leucine, 2.08 ± 0.13 mg arginine, 1.54 ± 0.01 mg isoleucine and 1.06 ± 0.03 mg alanine). Two-step fermentation optimization was done with Saccharomyces cerevisiae and Escherichia coli in Ulva hydrolysate following the SWH, with ethanol yield of 4.67 ± 0.76 mg g −1 DW Ulva . Based on these process results, some economics and sustainability indicators were estimated for large-scale macroalgae-based biorefinery. The required offshore areas for Ulva cultivation to satisfy the entire national demand in Israel for plant-based protein, char for electricity production (20% blend co-firing with coal), or ethanol for transportation (10% blend in gasoline), are 0.8%, 3.1% and 34.3%, respectively of the Israeli exclusive economic zone in the Mediterranean sea. The total revenue expected for the co-products derived from Ulva sp. via SWH varies between $0.26 and $1.06 kg −1 DW.